Effects of Apatinib on the “Stemness” of Non-Small-Cell Lung Cancer Cells In Vivo and Its Related Mechanisms - Bin Yang; Yan Wang; Zhuoying Chen; Yi-Ming Feng; Liang-Liang Shi (Canadian Respiratory Journal)
Objective. To investigate the effects of Apatinib on the “stemness” of lung cancer cells in vivo and to explore its related mechanisms. Methods. A xenograft model of lung cancer cells A549 was established in nude mice and randomized into a control group (n = 4) and an Apatinib group (n = 4). Tumor tissues were harvested after 2 weeks, and mRNA was extracted to detect changes in stemness-related genes (CD133, EPCAM, CD13, CD90, ALDH1, CD44, CD45, SOX2, NANOG, and OCT4) and Wnt/β-catenin, Hedgehog, and Hippo signal pathways. Results. Compared with the control group, the volume and weight of nude mice treated with Apatinib were different and had statistical significance. Apatinib inhibited the expressions of ABCG2, CD24, ICAM-1, OCT4, and SOX2 and upregulated the expressions of CD44, CD13, and FOXD3. Apatinib treatment also inhibited the Wnt/β-catenin, Hedgehog, and Hippo signaling pathways. Conclusion. Apatinib suppressed the growth of non-small-cell lung cancer cells by repressing the stemness of lung cancer through the inhibition of the Hedgehog, Hippo, and Wnt signaling pathways.